Bangladesh: Uncertain prospects - Ahmed, Raisuddin; Karim, Zahurul (International Food Policy Research Institute, 2006)
Bangladesh is one of the most impoverished countries in the world. Agriculture remains the primary source of income for about 60 percent of the population. Agricultural growth therefore holds the key to the nation’s pervasive poverty. So formidable are resource limitations, the climatic and environmental conditions, and the complexity of the country’s agricultural institutions that the pace of agricultural growth rests heavily on gains in productivity, especially those gains arising from research and development. Bangladesh’s achievements in agriculture and rural development have been significant since independence in 1971, and research and development have played a vital role in this achievement. This chapter focuses on the evolution of research policies and institutions, the priority given to agricultural research in resource allocation, the impact of agricultural research on productivity, and a vision for the future role of research.